Local public food - upgrading match between concepts and structures - Mikkola, Minna; Risku-Norja, Helmi (dk, 2012)
Maintains a high-level expert in Finland: Local food has grown into something like a social movement.The statement catches poignantly the broad social support for the concept of local food. However, public food represents a societal concept, loaded with expanding responsibilities of the welfare state not only to provide citizens with healthy but also sustainable meals. These include aspects of supporting local economy, more equitable trading relations and decreasing environmental impacts. Here the welfare state supports through its policies developmental trajectories for sustainable food systems. This paper analyses the concept of local food as it is understood by public procurers and examines the structural match of the supply and demand in public procurement. The paper is based on qualitative and quantitative data about public procurement of local food during the first decade of 21st millennium. The qualitative data stem from public caterers representing organizations across Finland, offering a valid view about the dependency of the size of the organization and its understanding of the concept of local food. The quantitative data have been collected by a survey covering the Finnish municipalities, and it shows the proportion of local food used by public catering in different parts of the country. The results suggest issues of structural development both in supply and demand and possibilities to understand the concept of local food in more functional ways than currently is the case.
Keywords: Ma; lähiruoka; elintarvikkeet; suurkeittiöt; public food; local food; public caterers; survey of local public food